2018
DOI: 10.3892/or.2018.6287
|View full text |Cite
|
Sign up to set email alerts
|

Deleted in malignant brain tumor 1 is a novel prognostic marker in colorectal cancer

Abstract: The gene deleted in malignant brain tumor 1 (DMBT1) encoding a large scavenger receptor cysteine-rich protein was originally identified based on its deletion in a brain tumor cell line. The DMBT1 protein is involved in mucosal immune defense, epithelial differentiation and tumor suppression. In the present study, the clinicopathologic significance of DMBT1 protein expression in stool and tissue samples of colorectal cancer (CRC) patients was evaluated. Western blot analysis of fecal DMBT1 was performed for pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
(31 reference statements)
3
12
0
Order By: Relevance
“…Besides, down‐expressed DMBT1 in invasive cholangiocarcinoma demonstrated the late stage of cholangiocarcinogenesis . In another study, LOH on marker D10S209 near the DMBT1 loci was observed to be a significantly poor prognostic factor, and DMBT1 loss in colorectal cancer was an independent unfavorable prognostic factor for cancer‐associated death and disease recurrence . Moreover, CSCC patients with positive DMBT1 expression had apparently higher 5‐year survival rate than those with negative DMBT1 expression in our study, suggesting that DMBT1 may not only participate in the progression of CSCC, but affect the prognosis of CSCC.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Besides, down‐expressed DMBT1 in invasive cholangiocarcinoma demonstrated the late stage of cholangiocarcinogenesis . In another study, LOH on marker D10S209 near the DMBT1 loci was observed to be a significantly poor prognostic factor, and DMBT1 loss in colorectal cancer was an independent unfavorable prognostic factor for cancer‐associated death and disease recurrence . Moreover, CSCC patients with positive DMBT1 expression had apparently higher 5‐year survival rate than those with negative DMBT1 expression in our study, suggesting that DMBT1 may not only participate in the progression of CSCC, but affect the prognosis of CSCC.…”
Section: Discussionsupporting
confidence: 53%
“…26 In another study, LOH on marker D10S209 near the DMBT1 loci was observed to be a significantly poor prognostic factor, 27 and DMBT1 loss in colorectal cancer was an independent unfavorable prognostic factor for cancer-associated death and disease recurrence. 28 Moreover, CSCC patients with positive DMBT1 expression had apparently higher 5-year survival rate than those with negative DMBT1 expression in our study, suggesting that DMBT1 may not only participate in the progression of CSCC, but affect the prognosis of CSCC. It was worth noting that the 5-year survival for stage II patients was indeed lower than expectation, which may be affected the multiple factors, including the small sample size (n = 37), severe stage (stage IIB: n = 27, stage IIA: n = 11), DMBT1 expression (negative: n = 36; positive: n = 1), and so on.…”
Section: Dmbt1 Overexpression Inhibited Proliferation and Promoted supporting
confidence: 46%
“…18 Loss of DMBT1 is associated with an increased risk of Crohn’s disease, metastasis, and cancer-associated death. 1921 High expression of DMBT1 promotes apoptosis of cancer cells in vitro and inhibits tumor progression in vivo. 22…”
Section: Introductionmentioning
confidence: 99%
“…Speci cally, DMBT1 was the most downregulated transcript, with a 133.4784-fold reduction, and ZNF780B was the most upregulated transcript, with the greatest fold change of 1657.641. Additionally, it has been reported that the overexpression of DMBT1 is related to biliary carcinoma [23] and colorectal cancer [24]. Moreover, ZNF780B expression has been correlated with hepatocellular carcinoma [25] and primary osteoarthritis [26].…”
Section: Discussionmentioning
confidence: 98%